Pengaruh Metode Pembelajaran Berbasis Proyek terhadap Hasil Belajar IPA Konsep Bunyi Kelas IV SDIT at-Taufiq Kota Tangerang - Sheilawati, Dhessela; Zulaini, Rizki; Rini, Candra Puspita (ARZUSIN, 2022)
This study aims to determine the effect of project-based learning methods on science learning outcomes for fourth grade students of SDIT At-Taufiq Tangerang City. This study uses a quasi-experimental method with the research design of Neonequivalent Control Group Design. The population subjects in this study were all class IV SDIT At-Taufiq Tangerang City, amounting to 58 students, by taking a sample of two classes of 58 students, namely class IV A, totaling 30 students as the experimental class. Data collection techniques using a test instrument consisting of 22 valid and reliable questions. For testing the pretest hypothesis in this study, the t-test was used, from the results of the t-test obtained calculated = 1.98 and table = 2.00, it can be concluded that there is no significant effect between the average pretest value of the control class and the experimental class. Meanwhile, for testing the posttest hypothesis, the t-test results obtained calculated = 6.167 and table = 2.00, it can be concluded that there is a significant effect between the average posttest value of the control class and the experimental class. This means that the fourth grade students' science learning outcomes using project-based learning methods are higher than using conventional learning methods.